Annotated catalogue of the types of Indo-Burmese non-marine Gastropoda deposited in the Faculty of Tropical Medicine, Mahidol University, Thailand. (3rd April 2019) - Ng, Ting Hui; Limpanont, Yanin; Chusongsang, Phiraphol; Chusongsang, Yupa; Panha, Somsak
ABSTRACT: Four decades after its publication, Rolf A.M. Brandt's 1974 monograph on the non-marine molluscs of Thailand remains the main authority on freshwater and estuarine species for Southeast Asia and includes up to 165 new species of snails and bivalves described by Brandt and colleagues in the same book and preceding publications. All the holotypes are lodged at the Forschungsinstitut und Naturmuseum Senckenberg in Germany, and are largely inaccessible to Thai and other Southeast Asian researchers, who rely heavily on the Brandt collection as a key reference. Paratypes were, however, donated to various other collections, including some in Thailand. We present the first catalogue of 45 paratypes of gastropods of the Brandt collection, described from Thailand, Laos and Cambodia, which are lodged at the Faculty of Tropical Medicine, Mahidol University, Thailand.